THE EFFECT OF MOTIVATION, WORK CULTURE, AND WORK FACILITIES ON THE PERFORMANCE OF CRAFTSMANS AT THE BLACKSMITH CENTER IN TERATAK RUMBIO JAYA - Ahmad Razilan; Zamhir Basem; Henrizal Henrizal (Jurnal Riset Manajemen Indonesia, 2022)
This study aims to determine the effect of motivation, work culture and work facilities on the performance of craftsmen at the blacksmith center teratak rumbio jaya. Sampling was carried out using the census method as many as 57 employees. Data analysis was carried out using multiple linear regression models. Based on the results of the simultaneous test, the variables of motivation, work culture, work facilities have a significant effect on the performance of the craftsmen of the Terrata Rumbio Jaya blacksmith center. Based on the partial test, the variables of motivation, work culture, work facilities have a significant effect on the performance of the blacksmith center at Teratak Rumbio Jaya. The contribution of the independent variable to the dependent variable is 30.6% while the remaining 69.4% is influenced by other variables not examined in this study.